Denosumab Related Osteonecrosis of Jaw: a Case Report - Marco Vinícius de Sales Lima; Jaqueline Rizzato; Daniella Varzea Gracindo Marques; Dárcio Kitakawa; Felipe da Silva Peralta; Alexandre Prado Scherma; Luis Felipe C. S. Carvalho (Stilus Optimus, 2018)
Background: This case report shows an affected postmenopausal patient with medicaments related osteonecrosis of the jaw injury associated with increased use of bisphosphonates and Prolia® (denosumab) for the treatment of osteoporosis. The mechanism of action of the receptor activates the denosumab of the nuclear-kB factor binding and makes nuclear-kB Factor, reducing bone volume and reabsorption in the trabecular and cortical bones and, consequently, decreasing an incidence of fractures and maintaining a bone formation. The bone physiology regulated by the hormones calcitonin, parathormone and vitamin D also undergoes interference. Methods: The injury was located around a dental implant in region #24 and #25 and the patient complained of pain, bleeding, oedema, and halitosis for more than two months, that the dental implant had been installed five years before. According to the clinical findings, the patient presented the exposed and necrotic bone in the region of #24 and #25 and with the radiographs found, it was observed as extensive bone destruction adjacent to the dental implant. Results: Patient was referred to the maxillofacial surgeon that performed the removal of bone sequestration and dental implant in the region affected. After that, the patient has been accompanied for a year. Conclusions: Patients taking medications for osteoporosis or cancer need to receive special attention from the dentist. Invasive procedures on the jaw bone of patients taking these medications may cause osteonecrosis of the jaw. When diagnosed, osteonecrosis of the jaw should be treated surgically in conjunction with antibiotic therapy and patients should be monitored.